Autoimmune encephalitis: an observational study from South India - Rithvik Ramesh; Philo Hazeena; Sundar Shanmugam; Shankar Venkatasubramanian; Santhosh Perumal; Vijaya Shankar; Pedapati Radhakrishna (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2023)
Abstract Background Ever since AE was acknowledged as a potentially treatable cause of encephalitis, it has been increasingly recognised worldwide. Data suggests that these disorders are under-recognized, which calls for an increased awareness of the varying clinical, laboratory, electrophysiological and radiological presentations of the different types of autoimmune encephalitis. This cross-sectional observational study included all patients diagnosed with AE, who presented to a tertiary care centre from June 2016 to January 2021. Data were collected including patient’s demography, clinical, laboratory, radiological and electrophysiology studies, management and outcomes. Results 31 study participants were included, of which 13 patients were anti-NMDA antibody positive, 12 patients were anti-LGI1 antibody positive, 2 patients were anti-CASPR2 antibody positive, 2 were positive for dual positive status (anti-LGi1 and anti-CASPR2), and one each for anti-GABA-B and anti-GAD 65. There was a marginal male predilection with overall seizures being the most common symptom (68%) followed by behavioural disturbance (64.5%), and impairment of consciousness (32.3%). Patients with Anti-NMDA encephalitis were likely to be young females, with CSF pleocytosis, a more protracted hospital course with more chances of relapse and residual disease, while the patients with anti-Lgi1 encephalitis were likely to be older males with a shorter, less severe hospital course. Conclusion The present study detailed the demographic, clinical, imaging, laboratory and EEG characteristics of 31 AE patients from a tertiary centre. The findings concurred with the literature and demonstrate the diverse spectrum of clinical manifestations of patients with AE, present with.